Sexual Symbols in Khasi folklore and its comparison with Indian Mythology: The Ramayana - Shabong, Daphysha M (International Journal of Language and Literary Studies, 2026)
A symbol has multiple meanings and some resemblance to what it is supposed to represent. The paper deals with the sexual symbol in Khasi folklore, focusing on the Khasi myth Ka Tiew Larun and the legend Ka Kshaid Dain Thlen, and on the Indian mythology of the Ramayana. Folklore is a word coined by William John Thoms in the periodical ‘The Athenaeum’ in 1846. Folklore is an academic discipline whose subject comprises the totality of literature historically transmitted orally or in imitation. The origin of the Khasis, or the Hynniew Trep (seven hut), is their heavenly abode through the golden ladder, or Sohpet bneng peak. Khasis is blessed with various folklore dealing with the myths and legends and folktales. A very few comparative works have been undertaken to analyse how sexual symbolism functions differently within the Khasi folklore and the Indian mythology. Using the qualitative methods of comparative textual methodology of feminisms, mythological criticism and psychoanalytical theory, this paper portrays how the bodily metaphors and natural elements show sexual symbols. The myths and legends of the Khasis portray the sexual symbol be the myth of Ka Tiew Larun were she uses the bamboo to quench her thirst but she became pregnant so the bamboo serves as a phallic symbol and the legend of Ka Kshaid Dain Thlen where the serpent, the cave serves as a symbol of sexual symbol. The paper also concentrates on the Indian mythology of Ramamyana, it is the greatest epic in Indian mythology. But this great epic can take the form of feminist thought, the position of woman in a patriarchal society. The paper portrays the value of woman, gender and the identity crises of woman in a male dominated society. It will examine the role of Sita, how she suppresses her identity, because of her husband, how she had to face all the challenges and she is the archetypal of all the woman. The paper argues that Khasi Folklore portray sexual symbol as Freud interpret in his Interpretation of Dreams, whereas Ramayana uphold patriarchal control through the ideals of chastity and sacrifice. The comparative analysis reveals that Khasi folklore and the Ramayana employ sexual symbolism differently to reflect their respective cultural structures. Khasi myths encode sexuality through natural symbols such as bamboo, snakes, and flowers, suggesting an organic and symbolic engagement with fertility and desire. In contrast, the Ramayana represents sexuality through the control and regulation of women’s bodies, particularly through Sita’s trials, exile, and chastity tests, thereby reinforcing patriarchal authority. While extensive scholarship exists on the Ramayana and feminist interpretations of Sita, limited academic attention has been given to Khasi sexual symbolism in comparative frameworks. There is a significant gap in interdisciplinary studies that juxtapose indigenous oral traditions of Northeast India with classical Indian epics to examine gender, sexuality, and power.